RESEARCH TRENDS OF AUGMENTED REALITY IN BIOLOGY LEARNING: CONTENT AND BIBLIOMETRIC MAPPING ANALYSIS - Asrizal Wahdan Wilsa; Hartono; Bambang Subali; Enni Suwarsi Rahayu (Malaysian Journal of Learning and Instruction)
Purpose - Through the use of content analysis, this study was aimed at identifying the patterns in research conducted during the past decade and investigating the bibliometric outcomes of articles focused on augmented reality (AR) utilization in biology learning.